2014
DOI: 10.1002/pbc.25070
|View full text |Cite
|
Sign up to set email alerts
|

Steroid‐induced ocular hypertensive response in children and adolescents with acute lymphoblastic leukemia and non‐hodgkin lymphoma

Abstract: The aim of this study was to evaluate intraocular pressure (IOP) associated with use of glucocorticoids in children and adolescents treated for acute lymphoblastic leukemia and non-Hodgkin lymphoma. We carried out a prospective descriptive study with measurement of IOP before treatment (D0), 8th (D8), 14th (D14), and 28 h days (D28) of treatment. We examined 12 patients, with two cases of ocular hypertension, and it was found a statistically significant difference between the means of IOP between D0 versus D8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Typically, these patients are administered relatively high doses of corticosteroid during chemotherapy. Importantly, several authors reported corticosteroid‐induced glaucoma in pediatric patients with hematological malignancies . de Queiroz Mendonca et al reported 12 patients with hematological malignancies who were administered 40 mg/m 2 prednisolone or 6 mg/m 2 dexamethasone for 28 days; two of the patients required topical treatment with eye drops for glaucoma.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Typically, these patients are administered relatively high doses of corticosteroid during chemotherapy. Importantly, several authors reported corticosteroid‐induced glaucoma in pediatric patients with hematological malignancies . de Queiroz Mendonca et al reported 12 patients with hematological malignancies who were administered 40 mg/m 2 prednisolone or 6 mg/m 2 dexamethasone for 28 days; two of the patients required topical treatment with eye drops for glaucoma.…”
Section: Discussionmentioning
confidence: 51%
“…Importantly, several authors reported corticosteroid‐induced glaucoma in pediatric patients with hematological malignancies . de Queiroz Mendonca et al reported 12 patients with hematological malignancies who were administered 40 mg/m 2 prednisolone or 6 mg/m 2 dexamethasone for 28 days; two of the patients required topical treatment with eye drops for glaucoma. Yamashita et al reported that IOP exceeded 21 mmHg in five Japanese children with ALL and that one of the patients developed optic neuropathy.…”
Section: Discussionmentioning
confidence: 54%
“…2,3 Cessation of the systemic corticosteroid typically results in the lowering of IOP to normal levels. 2,4 However, most of the diseases that necessitate systemic corticosteroid therapy in children, such as acute lymphoblastic leukemia, nephrotic syndrome, kidney transplantation, and inflammatory bowel disease, are chronic and/or potentially fatal, so any possible adverse effects from long-term systemic corticosteroid use are minor compared with the prospective benefit. Treatment consequently turns to topical antiglaucoma therapy to maintain IOP at normal levels.…”
Section: Discussionmentioning
confidence: 99%
“…5 The ocular hypertensive response has further been shown to be greater with oral dexamethasone than with oral prednisone. 4 This may be due to the fact that oral dexamethasone better penetrates the central nervous system and has a longer halflife, which is why it is the steroid of choice in the treatment of acute lymphoblastic leukemia. 6 It is conceivable that our patient's IOP was elevated for 14 days before his initial visit, as he had been symptomatic for headache for 14 days.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, children with glaucoma require timely intervention to avoid optic nerve damage. Children with cancer often receive glucocorticoid therapy, and thus have an increased risk of glaucoma . The discontinuation of glucocorticoid therapy, or the use of a lower dose, is the preferred approach for management of steroid‐induced glaucoma.…”
mentioning
confidence: 99%